Application of Intravascular Ultrasound in the Emergency Diagnosis and Treatment of Patients with ST‐Segment Elevation Myocardial Infarction. Issue 6 (7th October 2014) - Wang, Hong‐Xia; Dong, Ping‐Shuan; Li, Zhi‐Juan; Wang, Hong‐Lei; Wang, Ke; Liu, Xiang‐Yong
<x xml:space="preserve">Abstract</x> Purpose This study aimed to examine the application of intravascular ultrasound (IVUS) in ST‐segment elevation myocardial infarction (STEMI) patients with high thrombus burden (thrombus grade ≥3) undergoing emergency diagnosis and primary percutaneous coronary intervention. Methods Eighty STEMI patients were enrolled and randomly assigned to the IVUS‐guided group (38 patients) or non‐IVUS group (42 patients). Stent implantation was performed in non‐IVUS group patients. IVUS group patients were further divided into low‐risk and high‐risk patients on the basis of IVUS evaluation for determining whether stenting should be performed. Major adverse cardiac event (MACE) rates, changes in the left ventricular end‐diastolic diameter (LVEDD) and ejection fraction (EF) values, and stent numbers were examined during hospitalization, and follow‐up was performed at 1, 3, 6, and 12 months postoperatively. Results During hospitalization, there were no significant differences in the MACE rates, LVEDD, and EF values and in the follow‐up outcomes at 1, 3, 6, and 12 months postoperatively among the patients in the 2 groups (P > 0.05). A significantly lower number of stents were implanted in the IVUS group than in the non‐IVUS group patients (P < 0.05). Conclusion During the IVUS‐guided emergency intervention, enhanced antithrombotic therapy and best medical care for low‐risk STEMI patients may be feasible.